Classroom management for elementary teachers - Evertson, Carolyn M.; Worsham, Murrary E.; Clements, Barbara S.; Emmer, Edmund (Boston : Allyn and Bacon, 1997)
This book gives teachers the information and skills they need to establish management systems in today's rich, multicultural classroom, based on the authors' 30 years of research and experience in more than 500 classrooms. This best-selling book helps teachers plan, implement and develop the most basic classroom management task - to develop a smoothly running classroom that encourages learning. Written for the prospective or new elementary-level teacher, the book's content is ready to be applied in a classroom setting. The book addresses the planning decisions teachers must make including; arranging the physical space, establishing rules and procedures, planning and conducting instruction, encouraging appropriate behavior, addressing problem behavior, and using good communication skills with particular attention paid to the growth of ethnically diverse classrooms. All examples, checklists, case studies, and group activities are designed for the elementary level.
Includes bibliographical references.
Keywords: Classroom management; Education, Elementary